PENGARUH PENGGUNAAN MATERI AJAR MENULIS ESAI DALAM BAHASA INGGRIS BERBASIS PENDEKATAN PROSES-GENRE TERHADAP PENINGKATAN KEMAMPUAN MAHASISWA DI DALAM MENULIS ESAI BERBAHASA INGGRIS - Refnaldi, Refnaldi (Parameter, 2015)
The appropriate teaching/learning materials are needed in improving the students’ skills in writing an essay. This research aims at proving the effect of using the complete teaching/learning materials for writing essays based on the ‘process genre’ approach on the improvement of students’ ability in writing English essays. The design of the research was a pre-post control group experiment. The population of the research was students of English Language Teaching Study Program of State University of Padang and two classes of students were chosen through cluster sampling technique as the sample of research. The result of the research shows that the materials are effective enough in improving students’ skills in writing different types of essays and after several revisions, the final product of the materials consists of student book, student workbook, and teacher’s manual. Thus it can be concluded that this new materials can be well implemented in the teaching and learning essay writing at the English Language Teaching Study Program of State University of Padang.